2017
DOI: 10.1016/j.combustflame.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal evolution of harmonic disturbances on laminar, non-premixed flames: Measurements and analysis

Abstract: This paper analyzes the dynamics of harmonically forced, non-premixed flames, both experimentally and computationally. Prior theory has made a number of predictions on how wrinkles on non-premixed flamelets are excited by flow disturbances, convect axially, and evolve in disturbance magnitude, including setting up interference patterns in wrinkle disturbance magnitude. The objective of this study was to obtain measurements from forced flames to determine if these features are present, and to compare the gain/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In practice, the sound pressure increases linearly only in a certain range, depending on the electrical power applied to the sound source, and the combustion may have a discontinuous pattern [ 34 , 35 , 36 ]. Some works have described unpredictable wrinkling [ 37 , 38 ] or bifurcation [ 39 , 40 ] of the flame.…”
Section: Fire Extinguishingmentioning
confidence: 99%
“…In practice, the sound pressure increases linearly only in a certain range, depending on the electrical power applied to the sound source, and the combustion may have a discontinuous pattern [ 34 , 35 , 36 ]. Some works have described unpredictable wrinkling [ 37 , 38 ] or bifurcation [ 39 , 40 ] of the flame.…”
Section: Fire Extinguishingmentioning
confidence: 99%
“…Some research carried out showed that an increase in the average mass loss rate of fuels was observed with increasing sound pressure. Unpredictable flame wrinkling was reported in [48], [49], and its bifurcation was described in [50], [51]. From the analysis of research papers [52], [53], it can be inferred that the average flow effect is a significant factor in flame control.…”
Section: Introductionmentioning
confidence: 99%
“…The process of flame stream rupture due to acoustic waves is described in [51]. Wrinkling of the flame is presented in [52,53], and its bifurcation in [54,55].…”
Section: Introductionmentioning
confidence: 99%